Numerical heat transfer investigation in solar air heater channel with Wavy-Baffles - Promvonge, Pongjet; Noothong, Watcharin; Thianpong, Chinaruk (My University, 2014)
A numerical study is conducted to investigate the turbulent periodic flow and heat transfer characteristics in a channel fitted with sinusoidal wavy-baffles placed on upper and lower walls. The finite volume method is introduced and implemented with the SIMPLE algorithm. The flow structure, friction factor and heat transfer characteristics for different wavy-baffle configurations are evaluated. According to numerical result, the maximum thermal performance is found to be 1.22–1.66 times to smooth channel corresponding to the baffle a/H=0.75 and b/H=0.10. Consequently, the application of wavy-baffles can be utilized effectively to enhance the thermal performance of solar air heater.
Keywords: Friction factor; Heat transfer; Numerical; Solar air heater; Turbulent flow; Wavy-baffle